Entrepreneurship Development of Women Farmers Luhur Lestari Group in RT 01 RW 02 Cipicung Village, Baleendah District, Bandung Regency - Renosori, Puti; Prasetyaningsih, Endang; ., Selamat; Arif Nurrahman, Ahmad (KnE Social Sciences, 2023)
The main objective of the entrepreneurship development program at KWT Luhur Lestari is to utilize the potential of existing resources into productive activities that add value to the family economy. The first program was carried out by improving organic waste management, namely composting waste as well as urban farming with the organic tower garden (OTG) method. The second program was to improve culinary business skills in processing crops, especially cassava. So far, most of the crops are sold raw to collectors at low prices or processed into traditional foods. The method applied in implementing this community empowerment program is the participatory approach method, which means that partners are involved in every stage of the activity. The activities carried out are improving food processing skills, training in simple financial administration, and online marketing. Improvement of skills is done by the direct practice of making food so that the food has a good taste, is more interesting, creative, halal and thayyib (good for body health). This empowerment program has succeeded in increasing the entrepreneurship of “sublime sustainable” KWT members. KWT “sublime sustainable” has created a business division, whose members are active in entrepreneurship. Furthermore, assistance is carried out through discussions to overcome obstacles, evaluation of business activities, and food diversification. This empowerment has improved the family economy and KWT. Keywords: empowerment, OTG, entrepreneurship